Exploring Mimicry and Double Conscious Identity: A Study on Educational Imperialism through NCERT English Textbook Marigold (Grade 4), Honeydew (Grade 8), and Flamingo (Grade 12) - Angelina Rose Johnson (ILN Journal: Indian Literary Narratives, 2024)
This article investigates the manifestations of intellectual colonisation within students by examining the influence of NCERT English textbooks and the Indian education system. The study explores the shaping of students’ thoughts, values, and perceptions through carefully curated content that reinforces Eurocentric norms, ideologies, and narratives. This influence, in turn, affects how students perceive themselves, their culture, and the world around them. The selected texts for examination in this study are NCERT’s Grade 4 Marigold, Grade 8 Honeydew, and Grade 12 Flamingo. This study traces the colonial system of education in India and how the advent of English came about as a medium of communication and as a product of colonialism seeping into our Indian culture, leading to acculturation through the system of education. This article looks at how Bhabha’s concept of Mimicry and Du Bois’s concept of Double consciousness are used to critique texts and narratives in English textbooks to elucidate how both these concepts uncover power structures, the negotiation of cultural identities and the nuanced ways in which individuals navigate the educational landscape.